Hierarchical control of discrete-event systems : a new command and control design based on feasible system decomposition - Ngo, Quang Ha. (2013)
A new operational design for hierarchical control of discrete-event systems is proposed. The design brings the structure of command and control from concept to realization for on-line control operation. For a command reference input, the condition for output control feasibility of a discrete-event system modeled by a Moore automaton is characterized; and a system decomposition of a suitably structured Moore automaton into a controllable subsystem and an uncontrollable subsystem is formulated. Based on these results, the new command and control design for controller operation is realized and discussed.